Intra-abdominal drainage following pancreatic resection: A systematic review - Čečka, Filip; Loveček, Martin; Jon, Bohumil; Skalický, Pavel; Šubrt, Zdeněk; Neoral, Čestmír; Ferko, Alexander (World journal of gastroenterology, 2015)
AIM: To study all the aspects of drain management in pancreatic surgery. METHODS: We conducted a systematic review according to the PRISMA guidelines. We searched the Cochrane Central Registry of Controlled Trials, EMBASE, Web of Science, and PubMed (MEDLINE) for relevant articles on drain management in pancreatic surgery. The reference lists of relevant studies were screened to retrieve any further studies. We included all articles that reported clinical studies on human subjects with elective pancreatic resection and that compared various strategies of intra-abdominal drain management, such as drain vs no drain, selective drain use, early vs late drain extraction, and the use of different types of drains. RESULTS: A total of 19 studies concerned with drain management in pancreatic surgery involving 4194 patients were selected for this systematic review. We included studies analyzing the outcomes of pancreatic resection with and without intra-abdominal drains, studies comparing early vs late drain removal and studies analyzing different types of drains. The majority of the studies reporting equal or superior results for pancreatic resection without drains were retrospective and observational with significant selection bias. One recent randomized trial reported higher postoperative morbidity and mortality with routine omission of intra-abdominal drains. With respect to the timing of drain removal, all of the included studies reported superior results with early drain removal. Regarding the various types of drains, there is insufficient evidence to determine which type of drain is more suitable following pancreatic resection. CONCLUSION: The prophylactic use of drains remains controversial. When drains are used, early removal is recommended. Further trials comparing types of drains are ongoing.
Keywords: výsledek terapie; drenáž; rizikové faktory; Pancreatectomy; Time Factors; pankreatická píštěl; Pancreatic Fistula; Device Removal; Humans; design vybavení; odstranění implantátu; Risk Factors; pankreatektomie; Equipment Design; Treatment Outcome; lidé; časové faktory; Drainage